Logika Religius-Komunal di Ceruk Syariah: Platform Transportasi Daring dan Tata Kelola Tenaga Kerja Muslim di Indonesia - Bobby Ferly; Muchlis Bahar; Zainal Azwar (BISMA : Business and Management Journal, 2026)
This article examines how digital platforms organize Muslim gig labor in Indonesia amid competing market, corporate, and religious logics, and evaluates their organizational design through the lens of maqāṣid al-sharīʿah. Reframing the question from whether the gig economy is permissible toward how platform labor is actually governed within religious regulation, the study employs qualitative content analysis of credible Indonesian media reporting from 2024 to 2025, together with policy and platform documents. A three-family coding framework, derived from algorithmic human resource management, maqāṣid, and work-identity theory, guided the analysis. Findings show that mainstream platform governance is dominated by algorithmic fee structures and partnership framing that drivers contest through sustained collective action, reflecting an unresolved tension between market and corporate logics. A religious-communal logic is empirically present but segregated into sharia platforms such as Zendo, Ojesy, and Shejek rather than integrated into dominant players. Maqāṣid evaluation indicates that protection of property is most eroded, while collective agency predominates and loyalty appears as a discursive construction. The study refines institutional-logics theory by theorizing religious regulation as a third, currently segregated logic.